Elementos de regulação e microRNAs envolvidos na modulação dos níveis de hemoglobina fetal em indivíduos portadores de beta-hemoglobinopatias - Carrocini, Gisele Cristine de Souza [UNESP] (2015)
High levels of Hb F in adulthood may have beneficial effects for sickle cell anemia and beta-thalassemia. Some of the genetic elements that act in the regulation of Hb F expression are transcription factors and microRNAs. The aim of this study was to use phylogenetic footprinting to screen transcription factors that have binding sites in the γ-globin genes' noncoding regions, and miRNAs candidates to modulating Hb F levels, also evaluating the expression of microRNAs selected from in silico analyses in different groups with distinct profiles of Hb F expression. In silico analysis to screening of transcription factors were performed using bioinformatics tool VISTA, comparing the sequences of HBG1 and HBG2 genes in species of the Old and New World primates with the Homo sapiens sequences. The screening of predicted microRNAs to regulation of γ-globin genes was performed using public databases of microRNA. For the expression analyses of the selected microRNAs, we analized thirty-eight peripheral blood samples, divided into five groups: control group, sickle cell anemia using or not hydroxyurea (HU), and beta-thalassemia with and without allele β0. All samples were tested to hemoglobinopathies by classical diagnostic tests, quantification of globin fractions by chromatography and molecular analyses for genotyping of sickle cell anemia (PCR-RFLP) and beta-thalassemia (PCR-AE and genomic sequencing), and the characterization of haplotypes βS and β-Tal (PCR-RFLP). The reticulocytes were isolated from whole blood and submitted to microRNAs extraction. The analyses of the microRNAs expression were performed by real-time PCR (RT-PCR and qPCR). In silico analyses showed 13 transcription factors conserved between the analyzed species, which have binding sites in non-coding regions of both γ-globin genes, involved in regulating of the Hb F expression: BP1, CDC5, c-MYB, COUPTFII, CP2, GATA-1, GATA-2, NF-E2...